Use of Hydrogen Peroxide in Finfish Aquaculture - Roy P. Yanong (EDIS)
FA157, a 6-page fact sheet by Roy P. E. Yanong, uses a question-and-answer format to discuss how to use the hydrogen-peroxide based product 35% PEROX-AID ® as aquaculture treatment. Includes references. Published by the UF Program in Fisheries and Aquatic Sciences in the School of Forest Resources and Conservation, December 2008.